Hemostasis parameters in patients after coronary artery bypass surgery for stable angina - N. S. Lisyutenko; N. A. Morova; V. N. Tsekhanovich (Архивъ внутренней медицины, 2019)
The objective of research is to assess the significance of hemostatic profile in the postoperative period after coronary artery bypass surgery for predicting the one-year functioning of the grafts.Materials and methods. 46 men, who had coronary artery bypass surgery (CABS) for stable angina, were examined. 23 of them had 2 type diabetes mellitus (DM2), 23 of them did not have diabetes mellitus. All patients underwent fibrinogen, soluble fibrin monomer complex, D-dimer, induced platelet aggregation and lupus anticoagulant blood tests on the 14th day after surgery. The patients had coronary and bypass graft angiography for the assessment of graft patency a year after surgery.Results. During the postoperative period, there were no statistically significant differences between patients with DM2 and patients without DM2 in the results of the above hemostatic profile tests (p value for the Mann-Whitney test is >0.05). Lupus anticoagulant was detected in 9 patients with DM2 and in 12 patients without DM2 (p value for Fisher’s exact test is 0.554). 10 patients with DM2 and 6 patients without DM2 had graft occlusions a year after surgery; the differences for this sign were not statistically significant (p value for Fisher’s exact test is 0.18). Fibrinogen, soluble fibrin-monomer complex, D-dimer, and induced platelet aggregation tests did not demonstrate prognostic significance in relation to graft occlusions in both groups of patients (p for χ2 in the logistic regression model is >0.05). The factors associated with higher risk of graft occlusion in patients with DM2 were high ratio between screening and confirmatory test for the detection of lupus anticoagulant (odds ratio 2.27; 95% -confidence interval 1.119-1.238; p <0.05). Conclusion. After coronary bypass surgery, the one-year risk of graft thrombosis is higher in patients with DM2 and high positive LA activity.